2018
DOI: 10.1093/jat/bky040
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Ricinine and Abrine in Human Plasma by HPLC–MS-MS: Biomarkers of Exposure to Ricin and Abrin

Abstract: Ricin and abrin are toxic ribosome-inactivating proteins found in plants. Exposure to these toxins can be detected using the biomarkers ricinine and abrine, which are present in the same plant sources as the toxins. The concentration of the biomarkers in urine and blood will be dependent upon the purification of abrin or ricin, the route of exposure, and the length of time between exposure and sample collection. Here, we present the first diagnostic assay for the simultaneous quantification of both ricinine an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 23 publications
(40 reference statements)
0
11
0
1
Order By: Relevance
“…In another investigation, Wang et al [ 30 ] reported R 2 values of 0.9992 and 0.9988 with HPLC and LC–MS, of the standard solution of ricinine with different standard concentrations (27.7, 13.8, 6.92, 3.46, 1.73, 0.87, 0.43, 0.22, 0.11, 0.05, and 0 µg mL −1 ) and (500, 250, 125, 62.5, 31.2, 15.6, 7.8, 3.9, 1.8 and 0 ng mL −1 ), respectively. Isenberg et al [ 31 ] determined the correlation of ricinine standard by HPLC, which showed a high linearity of R 2 = 0.996 with different ricinine standard concentrations (200, 20.0, 0.800, and 0 ng mL −1 ). In this research, a linearity of R 2 = 0.9618 was obtained with different ricinine standard concentrations (0, 6, 8, 16, 20 μg L −1 ); we proceeded to quantify the ricinine in the extracts.…”
Section: Discussionmentioning
confidence: 99%
“…In another investigation, Wang et al [ 30 ] reported R 2 values of 0.9992 and 0.9988 with HPLC and LC–MS, of the standard solution of ricinine with different standard concentrations (27.7, 13.8, 6.92, 3.46, 1.73, 0.87, 0.43, 0.22, 0.11, 0.05, and 0 µg mL −1 ) and (500, 250, 125, 62.5, 31.2, 15.6, 7.8, 3.9, 1.8 and 0 ng mL −1 ), respectively. Isenberg et al [ 31 ] determined the correlation of ricinine standard by HPLC, which showed a high linearity of R 2 = 0.996 with different ricinine standard concentrations (200, 20.0, 0.800, and 0 ng mL −1 ). In this research, a linearity of R 2 = 0.9618 was obtained with different ricinine standard concentrations (0, 6, 8, 16, 20 μg L −1 ); we proceeded to quantify the ricinine in the extracts.…”
Section: Discussionmentioning
confidence: 99%
“…The plant originated alkaloid is used as stabilizers, skin-conditioning agents, emulsion, and surfactants in cosmetics [36]. Due to its relatively high toxicity (LD50 value for mice is 2-3 µg/kg), the Organization for the Prohibition of Chemical Weapons listed ricinine as a schedule 1 toxic chemical [37].…”
Section: Suspect and Non-target Screeningmentioning
confidence: 99%
“…To enable ricin identification, ricinine, a small alkaloid also found in castor bean seeds with higher levels compared to that of ricin, was suggested as a surrogate marker for ricin intoxication [ 10 ]. Indeed, the detection of ricinine in urine or serum was reported in an in vivo model for ricin intoxication [ 17 , 18 , 19 ] as measured in rat urine at least 48 h post exposure [ 18 ]. However, this approach may cause false positive results, due to the widespread use of ricinine-containing castor-oil in soaps, lubricants, dyes, pharmaceuticals, perfumes and food supplements.…”
Section: Introductionmentioning
confidence: 99%